2020
DOI: 10.1101/2020.08.11.243964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational changes and channel gating induced by CO2binding to Connexin26

Abstract: CO2 is the inevitable by-product of oxidative metabolism. Many physiological processes such as breathing1 and cerebral blood flow2 are sensitive to CO2. Historically, the physiological actions of CO2 have been regarded as being mediated exclusively via changes in pH. Here, we change this consensus by showing that the gap junction protein Connexin26 (Cx26) acts as a receptor for CO2 showing sensitivity to modest changes in PCO2 around the physiological norm3-6. Mass spectrometry analysis7 shows that CO2 carbamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…Cx26 also plays a role in mediating CO 2 -dependent modulation of the excitability of neurons in the substantia nigra and ventral tegmental area (Hill et al 2020). We have also recently demonstrated that K125 is indeed carbamylated and produced new high resolution cryoEM structures of Cx26 at different levels of P CO 2 (Brotherton et al 2020). Thus, carbamylation of Cx26 occurs and is involved in mediating the CO 2 -dependent control of physiologically important functions.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Cx26 also plays a role in mediating CO 2 -dependent modulation of the excitability of neurons in the substantia nigra and ventral tegmental area (Hill et al 2020). We have also recently demonstrated that K125 is indeed carbamylated and produced new high resolution cryoEM structures of Cx26 at different levels of P CO 2 (Brotherton et al 2020). Thus, carbamylation of Cx26 occurs and is involved in mediating the CO 2 -dependent control of physiologically important functions.…”
Section: Introductionmentioning
confidence: 80%
“…We have also recently demonstrated that K125 is indeed carbamylated and produced new high resolution cryoEM structures of Cx26 at different levels of PnormalCO2 (Brotherton et al . 2020). Thus, carbamylation of Cx26 occurs and is involved in mediating the CO 2 ‐dependent control of physiologically important functions.…”
Section: Introductionmentioning
confidence: 99%
“…While the mutational analysis strongly suggests carbamylation as a mechanism, it is not definitive. Recently however we have produced mass spectrometry evidence for the carbamylation of K125, and the consequent changes in channel gating in very high resolution cryoEM structures of Cx26 at different levels of PCO2 [70].…”
Section: Control Of Breathing and Identification Of A New Biological Sensing Molecule For Co2mentioning
confidence: 99%
“…There is a population of specialized glial cells present in a circumscribed nucleus-the caudal parapyramidal area that directly detect CO 2 via Cx26 and regulate breathing via the release of ATP [39]. Very recently, we have taken this down to the atomic level by solving cryoEM structures for Cx26 at different levels of PCO 2 to directly demonstrate the carbamylation mechanism and understand the conformational changes trigged by CO 2 -binding that lead to channel gating [40].…”
Section: Microelectrode Biosensors For Atp: Chemosensory Control Of Bmentioning
confidence: 99%